(untitled) (Materiali di Estetica. Terza serie, 2024)
The author reviews "Corpo, spazio, architettura: Fenomenologia dell’esperienza spaziale," edited by Matteo Vegetti and Fabrizia Bandi. The book examines the philosophical underpinnings of spatial experience through a phenomenological lens, engaging with both traditional and contemporary notions of how space, body, and architecture interconnect. The author highlights the text’s exploration of how architects and designers might integrate phenomenological insights into their work, transforming space from mere physical dimensions into lived, experienced reality. The review appreciates the book’s thematic organization, which starts with foundational theories from Merleau-Ponty and expands through discussions on virtual spaces and the future of architecture in the digital age. Through this anthology, readers gain a comprehensive view of the architectural implications of phenomenological thought, making it a critical resource for anyone involved in the conceptualization and design of space.